RUBBER DAM- IT'S PRESENT AND FUTURE USE AMONG DENTAL STUDENTS - SARANIYA PACKIRI,; DEEPA GURUNATHAN, (International Journal of Pharma and Bio Sciences, 2016)
Introduction: Rubber dam is universally acknowledged as a mandatory adjunct particularly during endodontic treatment. It offers many advantages, despite that it is still being ignored. Even thugh students undergo meticulous training in placement of rubber dam during their undergraduate training, there is still disincentive use of rubber dam in general practice, the reason for this is not entirely clear. Aim: The aim of this study was to evaluate the general attitude of third year, final year dental students and interns towards rubber dam usage in patients. Materials and methods: Pre validated closed ended questionnaire was distributed among third year, final year dental students and interns. Obtained datawere entered into an electronic database and statistical analysis was done using SPSS v20. Results: Out of the 130 questionnaire distributed, 107 were returned, and 23 students were not willing to participate in this study. 37.4% believe it’s a helpful tool and use rubber dam in clinic. 45.8% students felt that patient’s do not like it, thereby resulting in its disincentive use in future dental practice (26.2%). Conclusion: Even though dental students receive a satisfactory education about rubber dam, further emphasis should be placed on complications and mishap arising by not using it in private practice. Within the limitations of this study, it can be deduced that perceptions of dental students on rubber dam usage must be improved and strategies must be developed to implement it and improve the quality of dental treatment.